PENGARUH PROMOSI PENJUALAN, SLOGAN PRODUK, DAN KEPUASAN PELANGGAN TERHADAP KEPUTUSAN PELANGGAN MEMBELI PRODUK GAS PADA PT. TASYA GASINDO MEDAN - Pebrius Ginting; Nur Aisyah Nasution; Devi Novita Sari; Ryan Haganta Sebayang (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2020)
The purpose of this research is to find out and analyze influence of sales promotion, product slogan, and customers satisfaction, to customer decision at PT. Tasya Gasindo Medan. The data of this research is primary data which was obtained from the answers of 97 respondents with accidental sampling method. Data collection techniques used in this study used questionnaire and interview techniques. Data analisis techniques in this study used multiple linear regression classical assumption test, hypothesis test (t test andFf test) and the coefficient of determination. Data processing in this study used the SPSS (statistic package for the social sciences) program version 23. The results of this study indicates that particially promotion has a positive and significant effect on the customers decision PT. Tasya Gasindo Medan, particially it is known product slogan has a positive and significant effect on the decision PT. Tasya Gasindo Medan, particially that customers satisfaction has a positive and significant effect on the customers decision PT.Tasya Gasindo Medan and simultaneosly it is known that promotion, product slogan, customers satisfaction, together have a positive significant effect on the customers decision of PT. Tasya Gasindo Medan.